Solute carrier family 2 member 1 is involved in the development of nonalcoholic fatty liver disease12. Issue 2 (27th November 2012) - Vazquez‐Chantada, Mercedes; Gonzalez‐Lahera, Aintzane; Martinez‐Arranz, Ibon; Garcia‐Monzon, Carmelo; Regueiro, Manuela M.; Garcia‐Rodriguez, Juan L.; Schlangen, Karin A.; Mendibil, Iñaki; Rodriguez‐Ezpeleta, Naiara; Lozano, Juan J.; Banasik, Karina; Justesen, Johanne M.; et al.
Abstract Susceptibility to develop nonalcoholic fatty liver disease (NAFLD) has genetic bases, but the associated variants are uncertain. The aim of the present study was to identify genetic variants that could help to prognose and further understand the genetics and development of NAFLD. Allele frequencies of 3, 072 single‐nucleotide polymorphisms (SNPs) in 92 genes were characterized in 69 NAFLD patients and 217 healthy individuals. The markers that showed significant allele‐frequency differences in the pilot groups were subsequently studied in 451 NAFLD patients and 304 healthy controls. Besides this, 4, 414 type 2 diabetes mellitus (T2DM) cases and 4, 567 controls were genotyped. Liver expression of the associated gene was measured and the effect of its potential role was studied by silencing the gene in vitro. Whole genome expression, oxidative stress (OS), and the consequences of oleic acid (OA)‐enriched medium on lipid accumulation in siSLC2A1‐THLE2 cells were studied by gene‐expression analysis, dihydroethidium staining, BODIPY, and quantification of intracellular triglyceride content, respectively. Several SNPs of SLC2A1 (solute carrier family 2 [facilitated glucose transporter] member 1) showed association with NAFLD, but not with T2DM, being the haplotype containing the minor allele of SLC2A1 sequence related to the susceptibility to develop NAFLD. Gene‐expression analysis demonstrated a significant down‐regulation of SLC2A1 in NAFLD livers. Enrichment functional analyses of transcriptome profiles drove us to demonstrate that in vitro silencing of SLC2A1 induces an increased OS activity and a higher lipid accumulation under OA treatment. Conclusions: Genetic variants of SLC2A1 are associated with NAFLD, and in vitro down‐regulation of this gene promotes lipid accumulation. Moreover, the oxidative response detected in siSLC2A1‐THLE2 cells corroborated the antioxidant properties previously related to this gene and linked the most representative clinical characteristics of NAFLD patients: oxidative injury and increased lipid storage. (HEPATOLOGY 2013)